2001
DOI: 10.1094/phyto.2001.91.7.621
|View full text |Cite
|
Sign up to set email alerts
|

Combining Biocontrol Agents to Reduce the Variability of Biological Control

Abstract: Two biocontrol agents, a yeast (Pichia guilermondii) and a bacterium (Bacillus mycoides), were tested separately and together for suppression of Botrytis cinerea on strawberry leaves. The aims of the research were to determine whether the use of their combination would broaden the environmental conditions under which biological control is effective, and to test the hypothesis that it would reduce the variability of control efficacy under diverse conditions. Applied separately, the biocontrol agents significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
104
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(128 citation statements)
references
References 35 publications
8
104
0
5
Order By: Relevance
“…Moreover, the effect of the these factors and their interaction were insignificant (Table 2). This indicates that the control efficacy achieved by with Z1 was independent of the environmental conditions as previously reported by Guetsky et al (2001) against B. cinerea. This result could be explained by the environment of the wound which may protect the antagonistic yeast against from the adverse effects of the environmental factors studied here or alternatively by the time lapse between biocontrol agent application and pathogen inoculation.…”
Section: Combined Effect Of Temperature and Relative Humidity On Lesisupporting
confidence: 80%
“…Moreover, the effect of the these factors and their interaction were insignificant (Table 2). This indicates that the control efficacy achieved by with Z1 was independent of the environmental conditions as previously reported by Guetsky et al (2001) against B. cinerea. This result could be explained by the environment of the wound which may protect the antagonistic yeast against from the adverse effects of the environmental factors studied here or alternatively by the time lapse between biocontrol agent application and pathogen inoculation.…”
Section: Combined Effect Of Temperature and Relative Humidity On Lesisupporting
confidence: 80%
“…Lahlali (2006) reported a greater effect of humidity than temperature on the strain K population density on the apple surface under controlled laboratory conditions. Furthermore, Guetsky et al (2001) reported effects of temperature, relative humidity, and spray timing combinations on the biocontrol efficacy of Bacillus mycoides and Pichia guilermondii against Botrytis cinerea under laboratory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Fungicide treatment is the most common strategy used to control this pathogen, but the intensive use of fungicides such as thiabendazole (TBZ) and imazalil (IMZ) has led to the emergence of resistant strains of P. expansum (Spotts and Cervantes 1986;Vinãs et al 1993;Guetsky et al 2001). This fact, associated with growing public concern for human health and environmental hazards, highlights the need to develop alternative methods for controlling post-harvest diseases of apples (Wisniewski and Wilson 1992;Smilanick 1994).…”
mentioning
confidence: 99%
“…In the last few years, several reports have shown that co-inoculation of beneficial microorganisms could stimulate plant growth and/or increase plant disease resistance relative to inoculation with a single biocontrol agent (Raimam et al, 2007;Whipps, 2004). Although such combinations may enhance the level of plant protection against pathogen attack (Ezziyyani et al, 2007;Guetsky et al, 2001Guetsky et al, , 2002, the possible competitiveness between these micro-organisms has to be taken into consideration (Alabouvette et al, 2006). …”
Section: Interaction With Other Biocontrol Agentsmentioning
confidence: 99%